A Case Report of Collaborative Online International Learning in Nursing and Health Studies Between the United States and Japan. Issue 3 (14th May 2023) - Niitsu, Kosuke; Kondo, Akiko; Hua, Jing; Dyba, Natalia A.
Abstract: Collaborative online international learning (COIL) is an innovative and cost-effective pedagogy to develop cross-cultural awareness through digital technology across shared multicultural learning environments. We implemented our first COIL virtual exchange for undergraduate students at universities in the United States and Japan. We used Padlet for asynchronous discussions to build rapport among students at each institution and Zoom for synchronous discussions to deliver oral presentations. Feedback from students indicate an overall increase in intercultural competence and cultural sensitivity. COIL can provide meaningful, affordable, and feasible health education that enhances cultural understanding through virtual exchange.